2009
DOI: 10.1080/07853890903186168
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drug interactions on bleeding risk associated with warfarin therapy in hospitalized patients

Abstract: We conclude that co-medication in warfarin-treated in-patients is common and should be carefully evaluated to decrease the bleeding risk associated with warfarin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 25 publications
3
47
0
Order By: Relevance
“…The adjusted odds ratio (OR) for bleeding was highest for CYP2C9 inhibitors (OR 3.6, 95 % CI 2.4-5.6), while NSAIDs, coxibs and SSRIs were also associated with a significant bleeding risk (OR 2.6, 95 % CI 1.6-4.2; OR 3.1, 95 % CI 1.4-6.7; OR 2.6, 95 % CI 1.5-4.3, respectively). The OR for the platelet aggregation inhibitor group was 1.6 (95 % CI 0.8-3.1) [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adjusted odds ratio (OR) for bleeding was highest for CYP2C9 inhibitors (OR 3.6, 95 % CI 2.4-5.6), while NSAIDs, coxibs and SSRIs were also associated with a significant bleeding risk (OR 2.6, 95 % CI 1.6-4.2; OR 3.1, 95 % CI 1.4-6.7; OR 2.6, 95 % CI 1.5-4.3, respectively). The OR for the platelet aggregation inhibitor group was 1.6 (95 % CI 0.8-3.1) [15].…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has not been clearly explained, but recent epidemiological data have demonstrated that SSRIs could significantly increase the risk of gastro-intestinal bleeding [46,47]. According to some studies, the use of SSRIs among the population treated with coumarins seems to place patients at an increased risk of bleeding [15,48,49]. A warning should be added to make the physician aware of this interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For nonselective NSAIDs, studies reported ORs or risk ratios (RRs) from 1.9 (95% CI, 1.4-3.7) to 4.6 (95% CI, 3.3-6.5). [100][101][102][103]105,118 In addition, two studies reported a higher risk of bleeding with nonselective NSAIDs compared with COX-2-selective NSAIDs. 101,104 There was less consistency in the relationship between COX-2-selective NSAIDs plus VKAs vs VKA alone and bleeding outcomes, varying from a nonsignifi cant RR of 1.4 (95% CI, 0.44-4.30) to a signifi cant OR of 3.1 (95% CI, 1.4-6.7).…”
Section: Vka Drug Interactions To Avoidmentioning
confidence: 99%
“…[112][113][114] Similarly, some studies suggest that selective serotonin reuptake inhibitors, tramadol, acetaminophen, coenzyme Q, and ginger may increase the risk of bleeding, but these also require confi rmation. 103,105,106,116,117 Recommendations 3.8. For patients taking VKAs, we suggest avoiding concomitant treatment with NSAIDs, including COX-2-selective NSAIDs, and certain antibiotics (Grade 2C) .…”
Section: Vka Drug Interactions To Avoidmentioning
confidence: 99%